Crossing diaspora's borders: musical roots experiences and the Euro-American presence in Afro-Cuban religious music. - Warden, Nolan (International Library of African Music, 2010)
As a potentially more useful heuristic, I discuss what I call a musical "roots experience.” In doing so, I argue that recent Euro-American interest in Afro-Cuban music is a logical result of a search for a historicized cultural self, quite similar to that of African-Americans. In this way, the framework of a "roots experience” highlights experiential similarities across an ethnically diverse community of practitioners, whereas relying on the concept of the African Diaspora could possibly reinforce racial barriers.
Keywords: African Music